Revolutionizing Civil Servant’s Work Behavior through Flexible Working Spaces: Digital Transformation &Green Practices at the Ministry of Finance - Senja, Puput Yanita; Silviani, Wahyu Dian; Puspita, Rosana Eri (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: The COVID-19 pandemic forced the Ministry of Finance of the Republic of Indonesia to carry out a digital transformation by employing the concept of the Flexible Working Space (FWS) to ensure its civil servants can use the Work From Anywhere (WFA) system, including the Work From Home (WFH) system. These concepts are expected to help civil servants to optimize their performance. Background Problems: FWS has been practiced for two years, but detailed information on how the civil servants’ green work behavior has helped in maintaining their performance has not been investigated. Novelty: The researchers also studied how the digital transformation has changed the working practices among civil servants at the Ministry of Finance, and do they employ more green practices now? Discussion about the civil servants' green work behavior during this digital transformation is still limited. Research Methods: This study applied a qualitative technique to analyze the data obtained from an online qualitative survey, focus group discussions (FGD), observations and documentation. These research data were validated through a triangulation approach before being analyzed using the theory of planned behavior (TPB). Finding/ Results: The positive aspects of the Ministry of Finance’s digital transformation, which occurred during the pandemic, are civil servants can work faster, more efficiently, more flexibly, and they are more focused, but they have less contact with other people. While the identified disadvantage is that the internet network is occasionally unstable, thus disrupting the learning and discussion processes. The civil servants at the Ministry of Finance had used several green practices before the pandemic began, such as saving water, saving electricity, and to some extent they had gone plasticless and paperless. After the pandemic happened and FWS was implemented, these practices became more prominent, producing better results compared to the results before the pandemic. The pandemic also brought other advantages, including carbon emissions reductions and time savings. Conclusion: The FWS concept in the Ministry of Finance changed the work behavior related to the digital transformation, and the green work behavior of the civil servants. This is based on the TPB which includes attitudes, subjective norms, and behavioral control. Digital transformation using the FWS concept has had positive and negative impacts on the civil servants' green work behavior, and in maintaining their performance.